Efektivitas HE4 sebagai Metode Skrining Terbaru untuk Diagnosis Dini Kanker Ovarium - Amru Sofian; Hendra Perkasa; Ega Rahman Evsya; Riyan M Darundryo (Fakultas Kedokteran Universitas Riau, 2011)
The tumor marker CA125 is one of the currently used biomarkers to detect ovarian cancer. The tumormarker CA125 also elevated in other diseases. Human epididymis protein 4 is used as a new biomarker forearly detection of ovarian cancer. Human epididymis protein 4 is increased in almost all patients withovarian cancer and increased only slightly at a fraction of other diseases. Human epididymis protein 4 hasa better effectiveness in detecting ovarian cancer when combined with CA125. From the study of literaturefound that the combination of HE4 and CA125 had a specificity of 96.3% and 92.9% sensitivity.